2019
DOI: 10.1371/journal.pone.0221447
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perspectives on Public Health Medicine in South Africa

Abstract: South Africa (SA) is reforming its health system in preparation for an anticipated national health insurance (NHI) scheme that aims to improve the delivery of affordable, equitable, accessible health care. Public health (PH) language is explicit in the policy and skilled PH professionals would be expected to play a key role in its implementation. In South Africa, training of doctors as Public Health Medicine (PHM) specialists is funded by the state, yet there are few positions for PHM specialists in the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite the fact the public health system has been transformed into an integrated, comprehensive national service, failures in leadership, stewardship and management have led to inadequate implementation of good policies 19 . It is generally accepted that public health services in South Africa are not always of sufficient quality to be effective 20. External factors such as political preferences for the appointment of public health managers (HMs) have been reported to influence the employment of public health professionals 21 . Resulting management skill deficits have a detrimental effect on the quality of public health services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact the public health system has been transformed into an integrated, comprehensive national service, failures in leadership, stewardship and management have led to inadequate implementation of good policies 19 . It is generally accepted that public health services in South Africa are not always of sufficient quality to be effective 20. External factors such as political preferences for the appointment of public health managers (HMs) have been reported to influence the employment of public health professionals 21 . Resulting management skill deficits have a detrimental effect on the quality of public health services.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that public health services in South Africa are not always of sufficient quality to be effective 20 . External factors such as political preferences for the appointment of public health managers (HMs) have been reported to influence the employment of public health professionals 21 . Resulting management skill deficits have a detrimental effect on the quality of public health services.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is essential to note that the focus of this study is on DrPH programs in the United States, given the direct applicability and jurisdiction of CEPH. However, the challenge of standardizing public health practice and leadership is global, with similar discourse [ 25 ] taking place in South Africa [ 26 – 28 ], India [ 29 ], China [ 30 ], Korea [ 31 ], Southeast Asia [ 32 ], Ethiopia [ 33 ], and Pan Africa [ 25 ]. Many identity-defining efforts have been made by other accreditation agencies, such as the United Kingdom Public Health Register [ 34 ], the Board Certified in Public Health (CPH) [ 35 ], the National Consortium for Public Health Workforce Development [ 36 ], and the Council on Linkages Between Academia and Public Health Practice [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, endeavors have been made to incorporate the viewpoints of public health leaders in the development of education and healthcare systems. For instance, a qualitative study conducted in South Africa’s health system revealed that public health stakeholders perceived the public health profession to have a low standing due to an unclear identity [ 26 , 27 ]. In order to enhance the field, Zweigenthal et al (2018 & 2019) advocated for a curriculum redesign to improve recruitment efforts [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation